A comparison of fact sheets that promote preexposure prophylaxis (PrEP) use among men who have sex with men. Issue 3 (26th May 2020) - Ji, Yadong
ABSTRACT: Preexposure prophylaxis (PrEP) is an effective medicine against HIV transmission. PrEP can be especially beneficial in the men who have sex with men (MSM) communities. However, medical studies have associated MSM's PrEP use with undesired riskier behaviors (risk compensation), such as reducing condom use and acquiring more sexual partners. Fact sheets are important information sources for MSM to learn about PrEP and can potentially prevent risk compensation. This study compared three accessible fact sheets (the Truvada fact sheet, the CDC fact sheet, the FDA fact sheet) in terms of their effects on MSM's PrEP use intention and risk compensation intention (n = 600). The results showed that the CDC and the FDA fact sheets significantly encouraged higher PrEP use intention without provoking higher risk compensation intention. To promote PrEP use without raising risk compensation intention, fact sheets might be good information sources for the MSM population.